What are the limits of mathematical explanation? Interview with Charles McCarty by Piotr Urbańczyk - McCarty, David Charles; Urbańczyk, Piotr (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2016)
An interview with Charles McCarty by Piotr Urbańczyk concerning  mathematical explanation.
Keywords: mathematics; logic; mathematical explanation; limits of explanation; mathematical proof; proof-core; intuitionism; constructivsim; Gödel’s Incompleteness Theorems; intuitionistics mathematics; classical mathematics; Axiom of Choice